EVALUATION OF INHIBITORY ACTIVITY CHITOSAN NANOPARTICLES LOADED ON BASIL OIL AGAINST PSEUDOMONAS AERUGINOSA BIOFILM FORMATION - Obeid, Ahmed Abdul Kadhim; Jassim, Emad Hamdi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
The increasing resistance of Pseudomonas aeruginosa to antibiotics has complicated the treatment of infections due to its various virulence factors. One of its major pathogenic traits is the ability to form thick biofilms, which allow the bacteria to adhere to living or nonliving surfaces and enhance drug resistance. Consequently, exploring safe and effective therapeutic alternatives from plant sources has become essential for combating this multidrug-resistant pathogen. In this study, essential oil of Ocimum basilicum (BEO) was extracted via distillation and analyzed by GC-MS. The BEO was then loaded onto chitosan nanoparticles (BEOCSNPs) prepared using the ionic gelation method with tripolyphosphate (TPP). The nanoparticles were characterized using UV–vis, FTIR, SEM, and XRD techniques. Clinical isolates of Pseudomonas aeruginosa were obtained and identified with the VITEK-2 system. The minimum inhibitory concentrations (MICs) of BEO and BEOCSNPs were determined using a 96-well resazurin-based microdilution assay. The MIC of BEO ranged from 190 to 95 µg/mL, whereas the MIC of BEOCSNPs was significantly lower, ranging from 3.75 to 0.93 µg/mL. The inhibitory effects at sub-MIC concentrations were assessed by measuring optical density in a 96-well microplate using 0.1% crystal violet staining, which showed a significant decrease in biofilm formation. The biofilm inhibition activity of BEOCSNPs was notably higher in isolates P16 and P22, with inhibition percentages of 84.28% and 79.32%, respectively. In comparison, BEO alone inhibited P16 and P22 at 66.74% and 57.43%, respectively. These results indicate that Ocimum basilicum essential oil loaded onto chitosan nanoparticles exhibits superior inhibitory activity against biofilm formation of Pseudomonas aeruginosa compared to the essential oil alone.